Therapeutic Effects of Kefir Peptides on Hemophilia-Induced Osteoporosis in Mice With Deficient Coagulation Factor VIII - Yen, Chih-Ching; Liu, Yao-Wen; Chang, Gary Ro-Lin; Lan, Ying-Wei; Kao, Yung-Tsung; Cheng, Shin-Nan; Chen, Wei; Chen, Chuan-Mu (Frontiers in Cell and Developmental Biology, 2022)
Osteoporosis is a clinically prevalent comorbidity in patients with hemophilia. A preventive effect of kefir peptides (KPs) on postmenopausal osteoporosis has been proved. The aim of this study was to evaluate the therapeutic effect of KPs for the treatment of osteoporosis in coagulation factor VIII (FVIII) gene knockout mice (F8KO), a model of hemophilia A. In this study, male F8KO mice at 20 weeks of age were orally administered different doses of KPs for 8 weeks. The therapeutic effects of KPs were shown in the femoral trabeculae and the 4th lumbar vertebrae, which increased the trabecular bone mineral density (BMD), bone volume (Tb.BV/TV), and trabecular number (Tb.N) and decreased the trabecular separation (Tb.Sp), and they were also observed in the femoral cortical bones, in which the mechanical properties were enhanced in a dose-dependent manner. Characterization of receptor activator of nuclear factor κB ligand (RANKL), osteoprotegerin (OPG), and interleukin 6 (IL-6) demonstrated that the serum RANKL/OPG ratio and IL-6 levels were significantly decreased in the F8KO mice after the KP treatment. Tartrate-resistant acid phosphatase (TRAP) staining of mature osteoclasts indicated that the therapeutic effect of KPs in F8KO mice was associated with the functions of KPs to inhibit RANKL-induced osteoclastogenesis by reducing serum RANKL/OPG ratio and IL-6 secretion. The present study is the first to address the potentials of KPs for the treatment of hemophilia-induced osteoporosis in mice and it also provides useful information for the application of KPs as a complementary therapy for the treatment of osteoporosis in hemophilic patients.